Analyzing the Relationship between the dimensions of the strategic balance and reducing the strategic drift of the National Insurance Company /Applied Research - et. al., Farah naser musa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the research is to demonstrate the relationship between the strategic balance with its dimensions represented [ Information Technology, Employees, Internal processes, Insured (Customers) ]Strategic drift goal of his deportation to ]Lack of strategic planning, resistance to change, limited focus on the external environment, deterioration of performanceIn the National Insurance Company, a questionnaire was adopted as a tool to collect data and information from the research community, which numbered (64) Searched, and the statistical program was used( SPSS)In calculating( the arithmetic mean , the standard deviation, coefficient of variation , correlation coefficient, test T,variance X 2) The research reached the most prominent results, which are:There is a negative and inverse correlation between the dimensions of the strategic balance and the reduction of the strategic drift of the company, and there are also differences in the response of the research community to the paragraphs of the questionnaire according to the personal and functional variables (age, job location, number of years of service).